(untitled) (Annals of Medical Research, 2021)
Aim: Attention Deficit and Hyperactivity Disorder (ADHD) is the most frequently diagnosed psychiatric disorder in children. Only one study was found in literature which examined cutaneous findings in ADHD so far. The aim of the present study is to evaluate the cutaneous findings of children and adolescents diagnosed with ADHD and to compare the incidence of these findings with healthy controls. Material and Methods: Forty-six patients diagnosed with ADHD according to The Diagnostic and Statistical Manual of Mental Disorders fifth edition (DSM-V) criteria and 50 healthy controls with no ADHD symptoms that had similar characteristics to the patient group in terms of sociodemographic characteristics such as age and gender were included in the study. All the patients underwent whole body dermatological examination and pathological findings in the skin, hairy skin and nails in the patient and control group were recorded. Results: The most common finding in the patient group was found as onychophagy and/or periungual skin biting with a rate of 76.1%. In addition, statistically significant difference was found between the two groups in terms of xerosis, prurigo and allergy history. Conclusions: It is important to be careful in terms of cutaneous findings that may accompany ADHD in terms of both early treatment and also for preventing possible complications. In addition, determination of these findings will guide future studies in terms of identifying the common aetiology of ADHD and some cutaneous diseases.